Chapter 11 When the Margins Enter the Centre The Documentary Along the Borders of Turkey and Its YouTube Comments as Conflicting Constructions of Europeanity - Carpentier, Nico (Taylor & Francis, 2024)
This chapter uses a discourse-theoretical analysis to study two episodes of the documentary series Along the Borders of Turkey (2012), produced and broadcast by the Dutch public broadcaster VPRO. In 2017, the VPRO web team uploaded these episodes on YouTube, which allowed viewers to comment on these episodes. Supported by a theoretical reflection on the Europeanity discourse and its contingencies, and on the hegemonic or semi-hegemonic articulations of this discourse (with a central role allocated to European benevolence), this chapter shows the discursive consequences of the material dislocations caused by different migration flows in Cyprus and in Greece. The chapter analyses how the episodes represent the contradictions between European benevolence on the one hand, and popular intolerance and the workings of the border apparatus on the other. The analysis of these episodes thus shows how Europe is discursively constructed through the ceaseless interactions and unresolved tensions between the centre and the margins, articulating a Europe of both benevolence and intolerance.